Altered States: Performance and Perception in Form – A Kristján Guðmundsson Retrospective (Groundings Undergraduate, 2011)
This retrospective of the art of Kristján Guðmundsson will address how by refining the elements of painting and drawing, while simultaneously engaging the viewer in new and more thorough ways, the artists broadens the capacity to interact with art by confusing the viewer’s own immediate perception. Through unconventional, visual ways of measuring time and altering audio perception, the realm of the art becomes ours as well. By requiring us as viewers to relinquish our senses to fully participate in the work, it broadens one’s perception of art to the essential level of how one perceives the world.
Keywords: Kristján Guðmundsson; Retrospective; Painting; Drawing; Perception; Audio